Endothelial dysfunction in congenital adrenal hyperplasia due to 21-hydroxylase deficiency: current knowledge and novel biomarkers - Hubska, Joanna; Roszkowska, Zuzanna; Bobrowicz, Małgorzata; Iwaniuk, Sebastian; Rak-Makowska, Beata; Ambroziak, Urszula (Frontiers in Endocrinology, 2025)
Congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency (21OHD) is a complex endocrine disorder characterized by impaired cortisol synthesis and androgen excess. Beyond its hormonal and metabolic implications, CAH has been increasingly associated with an elevated risk of cardiovascular complications, including endothelial dysfunction, a critical precursor to atherosclerosis and a risk factor for cardiovascular and metabolic diseases. This review explores the current knowledge on endothelial function in patients with CAH, focusing on the interplay between chronic hormonal imbalance, prolonged glucocorticoid treatment, and associated metabolic disorders. We also discuss in vivo methods for assessing endothelial function alongside the potential utility of novel biomarkers, which may facilitate earlier identification of vascular dysfunction and stratification of cardiovascular risk. By summarizing emerging concepts in this field, we aim to highlight areas for future research and opportunities for improving long-term cardiovascular outcomes in individuals with 21OHD.